WARS BY MEMORY IN THE FORMER YUGOSLAVIA - Vuković, Đorđe (Politeia, 2020)
The culture of remembrance that dominates national communities and states that emerged after the civil war and disintegration of the former Yugoslavia is an area of daily conflict, and different and mutually exclusive interpretations of events from the past testify that Serbs, Croats, Bosniaks and other ethnic groups that share a common history remember and interpret it in completely different ways. Selective recollection, relativisation and fabrication of the past, reversal and forgetting, and falsification of facts about individual and group roles in contemporary history result in political conflicts in the present and could  potentially lead to future misunderstandings and conflicts, making the Balkans even more unstable and without any perspective.
Keywords: Culture of memory; Politicization of the past; Revisionism; Wars; Propaganda